A study to assess the prevalence of hypertension in children with nephrotic syndrome - M., Manasa; Prabhu, Anitha S.; Pai, Santosh; H., Kiran Raj (International Journal of Contemporary Pediatrics, 2019)
Background: Hypertension is been one of the most common co morbidity of this disease. It was mostly attributed to sodium retention, which is a major clinical feature of nephrotic syndrome. These mechanisms likely have a role in the development of hypertension in nephrotic syndrome, where hypertension may be difficult to control, and provide new therapeutic options for the management of blood pressure in the setting of nephrotic syndrome. Objective of study the prevalence of hypertension in children with NS and also the number of antihypertensive required to control it. Method: A Retrospective study of the hospital records of 100 children diagnosed with nephrotic syndrome admitted to Pediatric and Nephrology Ward at YMCH was accessed. Results: In our study 35 (35%) of them were Infrequent relapse nephrotic syndrome (IFNS) and 35(35%) were Frequent relapse nephrotic syndrome (FRNS) ,while 30 cases (30%) were First episode nephrotic syndrome (FENS). 65 cases were steroid sensitive, while 28 and 7 of them were steroid dependent and resistant respectively. Of the 100 study population 54 of them had hypertension while 46 of them did not develop it .Of the 54 hypertensive nephrotic syndrome children, 15 of them (28.%) required three anti hypertensives to control the pressure, while 19 (35%) and 20 (37%) required single and dual anti hypertensives respectively. Conclusion: Prevalence of hypertension is increasing among the children with nephrotic syndrome. Its more prevalent among the male then female FRNS, SRNS and SDNS are more prone to develop hypertension and also they needed two or more antihypertensives to control the hypertension, whereas hypertension in SSNS could be managed with single drug.